Microdialysis in Drug Development - Müller, Markus (AAPS Advances in the Pharmaceutical Sciences Series, 2013)
In vivo target site concentrations are probably the most important determinant of drug effects. Traditionally, linking drug concentrations to drug effects has been accomplished by modelling blood-derived data, mostly because a direct quantification of tissue concentrations has been beyond technical reach. Today, a direct measurement of target site concentrations is possible by employing microdialysis or complementary approaches such as imaging technologies. Microdialysis, initially conceived in the 1970ies, has become a standard tool in drug development. This comprehensive overview of current microdialysis technology covers general and disease-specific aspects of microdialysis by international experts in the field. It provides useful information for colleagues in academia and industry who are interested PK-PD aspects of drug development.